Oral Presentations Abstracts: COVID-19 MENTAL HEALTH IMPACTS. CHALLENGES FOR PSYCHIATRISTS - CRIȘAN, Cătălina; SUCIU, Bianca (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 COVID19 a new appeared virus determined a major impact worldwide on economic and social aspects and also on the mental state level. All countries are confronting with different behaviors of coping mechanism in particular buying excessive amounts of food, being more suspicious even with the family members, explained by an exacerbated surviving instinct, making stocks of unnecessary disinfectant sanitary products, even a chase for protective masks in some cases. Some of these aspects can be considered the effect of a mass psychosis, people being misinformed by television news, such as the concept of fake news having the intention of manipulation; others misinterpret the clear message, with severe consequences over the state of calm. During this crisis, all psychiatrists are facing new challenges such as sustaining the well-being of healthcare personnel, looking over the need of patient’s mental well-being, taking care of the psychological impact of quarantine, self-isolation and social stigma associated with COVID 19. An important aspect in Romania is represented by different cultural beliefs that are not usually present in other cultures but are characteristic in our population and can influence the outcome of the virus evolution. Protection from God, believing that spirituality and religiosity can become a fence in the confrontation with the virus, and these convictions could become a real impediment in understating and respecting the protocols and the rules of prevention. The ethical issue for psychiatrists is how to take into account patients’ beliefs in time of restrictive measures imposed by COVID19 pandemic? All in all, the COVID19 pandemic spread represents a real challenge for all employees in the medical system, but especially to psychiatrists, who should deal with patients whose capacity to understand the real/whole picture is deteriorated.